An outline and critical assessment of the role of planning laws in the regulatory framework of climate change adaptation in South Africa and Nigeria - Afinowi, Olubunmi Ayodele (Department of Public Law, 2019)
Climate change affects the natural and built environment, including all forms of development. The risks of climate change include severe alterations to the normal functioning of communities, including adverse effects on humans, infrastructure, land use, the built and natural environment. Due to these occurring and projected adverse effects, there is the need to develop resilience within communities, especially in areas of particular vulnerability. The point of departure of this research is that planning laws have a role to play in the adapting to, and building of resilience against, climate change. As such the work argues for an integration of climate change considerations into planning, environmental and related laws. The relevant laws will be examined to consider the extent to which they are suited to aid the adaptation process. The research entails a comparative approach through the analysis of planning laws in Nigeria and South Africa. It also involves qualitative empirical research into the effectiveness of planning laws as a means of adaptation to climate change. Planning law in Nigeria is very procedural and is limited to physical planning and ordering of the built environment. South Africa, on the other hand, has integrated sustainable development considerations into her planning legislation and it now encompasses spatial planning, integrated development plans, land use management and others. In both countries, however, there seems to be no express integration of climate change into planning laws, especially at the national level of government. The research also examines the legal aspects of climate change adaptation strategies in both countries. It found that in Nigeria in particular, there is no provision for inter-governmental cooperation to facilitate physical planning or climate adaptation action. In the case of South Africa, there is a well-structured intergovernmental collaboration regarding planning and land use management, which gives some consideration to climate change adaptation. However, the structure for cooperation is still being developed as seen in the draft National Adaptation Strategy and the proposed Climate Change Act. There is a need to reevaluate the relevant laws in both countries, with special consideration to the role of planning in adaptation to the adverse impacts of climate change on the natural and built environment.